6% Hydroxyethyl Starch (130/0.4) Versus Ringer Lactate Preloading Before Spinal Anesthesia for Cesarean Delivery: The Randomized, Double-Blind, Multicenter CAESAR Trial. Issue 3 (September 2015) - Mercier, F.J.; Diemunsch, P.; Ducloy-Bouthors, A.S.; Mignon, A.; Fischler, M.; Malinovsky, J.M.; Bolandard, F.; Aya, A.G.; Raucoules-Aimé, M.; Chassard, D.; Keita, H.; Rigouzzo, A.; et al.
Abstract : ( Br J Anaesth . 2014;113(3):459–467)